Spectroscopy of yttrium dimers in argon matrices: Low-Temperature Physics and Chemistry in Cryomatrice - Fang, Li; Chen, Xiaoyu; Shen, Xiaole; Liu, Yifei; Lindsay, D. M.; Lombardi, John R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The absorption and resonance Raman spectra of yttrium dimers (Y2) in argon matrices have been measured for the first time. The absorption spectrum (scattering depletion spectrum SDS) shows a weak, broad transition centered near 485 nm. Resonance Raman spectra obtained by exciting into this absorption band with several visible laser lines (465.5√496.5 nm) give a single, sharp progression with up to ten Stokes transitions. These data give we=184.4(4) cm-1, with we xe=0.30(3) cm-1, leading to a spectroscopic dissociation energy of De=3.5(4) eV. Comparison of our results with several ab initio calculations adds confirmation to the assignment of the ground state of Y2 to be 1∑g+ state.